Analisis Penggunaan Transaksi QRIS, Permodalan dan Literasi Digital dalam Memengaruhi Pendapatan UMKM Kuliner di Kota Denpasar - Ni Kadek Poppy Keristina; Anak Agung Bagus Putu Widanta (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are business groups that play a very significant role in the Indonesian economy, with the number of micro business actors estimated to be mostly engaged in the informal sector. This study aims to determine the influence of QRIS, capital, and digital literacy on the income of MSMEs in Denpasar. The research variable used was a dependent variable, namely the income of culinary MSMEs, while the independent variable used was the use of QRIS transactions, capital, and digital literacy. The sample from this study uses a non-probability sampling method, namely accidental sampling. The population in this study is culinary MSME actors in the city of Denpasar who are registered with the Denpasar City Cooperatives and MSMEs Office until the end of 2019 which totals 9,635 MSMEs with a sample of 99 which is calculated using the Slovin formula. The test uses multiple linear analysis, namely the simultaneous regression coefficient significance test (F test) and the partial regression beta coefficient significance test (t test). The results of the study show that 1). The simultaneous use of QRIS transactions, capital, and digital literacy has a significant effect on the income of culinary MSMEs in Denpasar City, 2). The use of QRIS transactions, capital, and digital literacy partially has a positive and significant effect on the income of culinary MSMEs in Denpasar City.